Mountaintop mining in Appalachia : understanding stakeholders and change in environmental conflict - Hirsch, Susan F. (Studies in conflict, justice, and social change., 2014)
Residents of the Appalachian coalfields share a history and heritage, deep connections to the land, and pride in their own resilience. These same residents are also profoundly divided over the practice of mountaintop mining-that is, the removal and disposal in nearby valleys of soil and rock in order to reach underlying coal seams. Companies and some miners claim that the practice has reduced energy prices, earned income for shareholders, and provided needed jobs. Opponents of mountaintop mining argue that it poisons Appalachia's waters and devastates entire communities for the sake of short-